2016
DOI: 10.3897/compcytogen.v10i4.10047
|View full text |Cite
|
Sign up to set email alerts
|

Physical mapping of immune-related genes in Yesso scallop (Patinopecten yessoensis) using fluorescent in situ hybridization

Abstract: The innate immune system plays a pivotal role in defending invasion of microorganisms for scallops. Previous studies on immune-related genes in the Yesso scallop, Patinopecten yessoensis (Jay, 1857) have mainly focused on characterization and expression pattern in response to bacterial challenge, no research has been carried out on the cytogenetic level yet. In the present study, eight fosmid clones containing the sequences of key immune-related genes (PyNFkB, PyTRAF2, PyTRAF4, PyTRAF7, PyMyd88-1, PyMyd88-3, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Zhang et al (2008a) successfully distinguished eight pairs of chromosomes of Chlamys farreri using eight fosmid clones. Li et al (2016) and Yang et al (2016) identified six and five pairs of chromosomes of Patinopecten yessoensis by six and eight fosmid clones, respectively. In some plant species, especially in those species with relatively small chromosomes, BAC-FISH had played an important role in chromosome identification and cytogenetic researches (Wang et al, 2007;Wai et al, 2010;Lee et al, 2020;Mendoza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2008a) successfully distinguished eight pairs of chromosomes of Chlamys farreri using eight fosmid clones. Li et al (2016) and Yang et al (2016) identified six and five pairs of chromosomes of Patinopecten yessoensis by six and eight fosmid clones, respectively. In some plant species, especially in those species with relatively small chromosomes, BAC-FISH had played an important role in chromosome identification and cytogenetic researches (Wang et al, 2007;Wai et al, 2010;Lee et al, 2020;Mendoza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some chromosome banding techniques have been applied to bivalves, e.g. C-banding was used for investigating the distribution and composition of heterochromatin ( Pasantes et al 1996 , Insua et al 1998 , Pauls and Affonso 2000 , Huang et al 2007b , García-Souto et al 2016 ), silver staining was used for localizing the nucleolus organizer regions (Ag- NORs ) ( Martínez-Expósito et al 1997 , Pauls and Affonso 2000 , Boroń et al 2004 ), fluorescence counterstaining with chromomycin A 3 or DAPI/PI used to identify the GC-rich or AT-rich heterochromatic regions ( Martínez et al 2002 , Huang et al 2007b , Zhang et al 2007c , Pérez-García et al 2010a , García-Souto et al 2015 , 2016 ), and fluorescent in situ hybridization ( FISH ) were used to localize 28S rDNA, 5S rDNA, and histone H3 gene to study karyotypic evolution on a variety of bivalves ( Insua et al 1998 , 2006 , Wang and Guo 2004 , López-Piñón et al 2005 , Huang et al 2006 , 2007a , Odierna et al 2006 , Zhang et al 2007b , Hu et al 2011 , Li et al 2016 , Yang et al 2016 , García-Souto et al 2015 , 2016 ). In addition, FISH was proved to be a valuable tool for mapping vertebrate telomere sequence ( TTAGGG ) n on chromosomes of some bivalves ( Wang and Guo 2001 , Huang et al 2007a , 2007b , García-Souto et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%